2008
DOI: 10.1007/s00441-008-0642-4
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular endothelial cell heterogeneity: general concepts and pharmacological consequences for anti-angiogenic therapy of cancer

Abstract: Microvascular endothelial cells display a large degree of heterogeneity in function depending on their location in the vascular tree. The existence of organspecific, microvascular-bed-specific, and even intravascular variations in endothelial cell gene expression emphasizes their high cell-to-cell variability, which is furthermore extremely adaptable to altering conditions. The ability of microvascular endothelial cells to respond dynamically to pathology-related microenvironmental changes is particularly appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 116 publications
0
81
0
Order By: Relevance
“…Both human and mouse tumors show considerable variation in the density, morphology and functionality of blood vessels (Langenkamp and Molema, 2009; Nagy et al., 2010). Furthermore, the endothelial cells of tumor blood vessels can display features –fenestration patterns, pericyte and inflammatory‐cell association, proliferation and apoptosis rates, and gene expression profiles – that vary not only among different tumor types or individual tumors, but also in a local–regional manner within a given tumor.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both human and mouse tumors show considerable variation in the density, morphology and functionality of blood vessels (Langenkamp and Molema, 2009; Nagy et al., 2010). Furthermore, the endothelial cells of tumor blood vessels can display features –fenestration patterns, pericyte and inflammatory‐cell association, proliferation and apoptosis rates, and gene expression profiles – that vary not only among different tumor types or individual tumors, but also in a local–regional manner within a given tumor.…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…Although human tumors display type‐specific vascular patterns, our understanding of such variability is mostly limited to histo‐pathological features (Langenkamp and Molema, 2009; Nagy et al., 2010). Different human cancers are variably sensitive to antiangiogenic drugs (e.g., inhibitors of endothelial TK receptors or antibodies that block vascular growth factors); furthermore, tumors of a generally refractory type may sporadically show dramatic responses to antiangiogenic drugs (Carmeliet and Jain, 2011b; Chung et al., 2010; Goel et al., 2011; Leite de Oliveira et al., 2011).…”
Section: Variability and Dynamics Of Stromal Cell Componentsmentioning
confidence: 99%
“…Indeed, clinical observation have suggested that the organ environment can influence the response of tumour to chemotherapies (Fidler, 2002;Killion, 1998) and orthotopic models allow to obtain a vasculature network similar to that of patient being useful for antivascular drug discovery. Interestingly, the vasculature of the tumour tends to acquire characteristics similar to those of the host environment (Langenkamp and Molema, 2009). The neovasculature of a specific tumour type can be indeed drastically different in terms of vascular architecture, microvascular density (MVD), permeability, vessel distribution, and gene expression, when the same tumour is grown in different locations of the body (Langenkamp and Molema, 2009).…”
Section: The Orthotopic Animal Modelmentioning
confidence: 99%
“…Interestingly, the vasculature of the tumour tends to acquire characteristics similar to those of the host environment (Langenkamp and Molema, 2009). The neovasculature of a specific tumour type can be indeed drastically different in terms of vascular architecture, microvascular density (MVD), permeability, vessel distribution, and gene expression, when the same tumour is grown in different locations of the body (Langenkamp and Molema, 2009). For example, the microvasculature of human glioblastoma implanted subcutaneously in nude mice became extensively fenestrated, with a large population of caveolae and a relatively high permeability, similar to the host endothelium of the subcutaneous space (Roberts, 1998).…”
Section: The Orthotopic Animal Modelmentioning
confidence: 99%
“…Furthermore, these effects might be tissue-specific (confined to lungs) as there might be important heterogeneity in type and density of specific receptors for vascular growth factors. 19 For these reasons, we recently have devised a complementory subacute thigh infection model (Ben-Ami R, et al AAC, in press) that could allow us the parallel study of the angiogenesis effects in two models that have different infection tissue and apace of evolution. If histopathology fails to show differences in angiogenesis in the treatment groups in the lung model, these outcomes may still be evident in the thigh model.…”
Section: Clinical Research Questionsmentioning
confidence: 99%